Transtopian moves: the rhizome in Jonas Carpignano's feature films Mediterranea (2015) and A Ciambra (2017) - Hudelist, Andreas; Justus Liebig University Giessen (My University, 2021)
Film comes to its fore as a cultural product, which frames social experiences, relations, and is constructed through these itself. Dealing with our current global and fluid so-ciety the analysis will focus on constructions of marginalized individuals who chal-lenge the viewers with their modulations and variations of identifications. Being (someone) evades the subject of becoming, which as an empty subject makes the po-tential of alternatives transparent and invites us to pursue lived connections, and not only in human-to-human relationships. Following Stuart Hall (1994), this is where a transtopian space is created, which not only collects and allows common knowledge, but also gives space to something new to emerge. The movies Mediterranea and A Ciambra by Jonas Carpignano show us a current picture of marginalized people as well as a rhizome of migration with line of flights.
Keywords: migration; lines of flight; Jonas Carpignano; rhizome; distribution of the sensible; ddc:300